100th Day of School with Yasmin - Faruqi, Saadia; Rahmalia, Debby (North Mankato, Minnesota : Picture Window Books, a Capstone imprint, 2025)
It is nearly the 100th day of school, and Yasmin wants to wear something special, but first she has to explain the holiday to her grandparents.
560
Keywords: Hundredth Day of School -- Juvenile fiction; Elementary schools -- Juvenile fiction; Muslim girls -- Juvenile fiction; Grandparents -- Juvenile fiction; Pakistani Americans -- Juvenile fiction; Hundredth Day of School -- Fiction; Elementary schools -- Fiction; Muslim girls -- Fiction; Grandparents -- Fiction; Pakistani Americans -- Fiction; Chidlren book